2014
DOI: 10.3389/fphys.2014.00312
|View full text |Cite
|
Sign up to set email alerts
|

Lipid regulation of BK channel function

Abstract: This mini-review focuses on lipid modulation of BK (MaxiK, BKCa) current by a direct interaction between lipid and the BK subunits and/or their immediate lipid environment. Direct lipid-BK protein interactions have been proposed for fatty and epoxyeicosatrienoic acids, phosphoinositides and cholesterol, evidence for such action being less clear for other lipids. BK α (slo1) subunits are sufficient to support current perturbation by fatty and epoxyeicosatrienoic acids, glycerophospholipids and cholesterol, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…; Ulluwishewa et al. ), membrane solute transporters (Ma and Eaton ; Dopico and Bukiya ), and even endocytic vessel formation and permeability (Grasso and Calderon , ). For hibernating bears dietary fat has special importance and significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Ulluwishewa et al. ), membrane solute transporters (Ma and Eaton ; Dopico and Bukiya ), and even endocytic vessel formation and permeability (Grasso and Calderon , ). For hibernating bears dietary fat has special importance and significance.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly in many mammalian species, dietary lipids have been shown to profoundly affect both membrane lipid composition and membrane function (including membrane permeability, activity of membrane – bound enzymes and receptors, and endocytosis and exocytosis (Abeywardena et al. ; Awad ; Dopico and Bukiya ; Spector and Yorek ; reviewed in Kummerow and Grasso and Calderon ), as well as tight junction permeability and occludin expression (Jiang et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol (CLR) is one of the major structural lipid components of animal cell membranes, a key mediator in lipid homeostasis, and precursor for the biosynthesis of steroid hormones, bile acids and vitamin D [26,17,22]. However, high levels of CLR in humans represent a risk factor for life-threatening cardio/cerebrovascular conditions, including heart attack and stroke [30].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we demonstrated that this site can also accommodate LTB4. Therefore, two endogenous lipids from different chemical groups (heterocyclic cholane steroids and linear leukotrienes) can share their site of action on an ion channel protein, an unusual phenomenon because lipid-sensing sites on ion channels, BK in particular, do not share ligands from different lipid species (1,43). The physiological implications of such overlap remain to be explored.…”
Section: Discussionmentioning
confidence: 99%